Different temporal dynamics of object-based attentional allocation for reward and non-reward objects - Song, Fangxing (J Vis, 2020)
Previous studies have confirmed that both non-reward objects (such as rectangles) and reward objects (such as banknotes) can guide the allocation of our attention; however, it is unclear whether the allocation mode of attention for reward objects is the same as for non-reward objects. This study aims to evaluate different modes of object-based attentional selection elicited by two types of objects: reward objects and non-reward objects. In our analysis, we used a two-rectangle paradigm in which two objects were presented visually. In a series of four experiments, we found a constant object-based effect with non-reward objects, such as rectangles and umbrellas, as stimuli in all of the stimulus onset asynchrony (SOA) conditions (Experiments 1 and 4), but the object-based effect disappeared only at longer SOA with reward objects such as monetary and food objects as stimuli (Experiments 2 and 3). Moreover, we found that monetary and food objects induced similar object-based effects. These results suggest that the temporal dynamics of object-based attentional allocation are different with respect to reward and non-reward objects, and different types of reward objects can guide attentional allocation in a similar way.